A new grinding strategy to improve the acoustic properties of railway tracks. (January 2018) - Kuffa, Michal; Ziegler, Daniel; Peter, Thomas; Kuster, Fredy; Wegener, Konrad
Rail grinding is a special application of high-performance dry grinding, which combines a number of special characteristics, such as high feed speed, good surface roughness and waviness and a high material removal rate. Since beginning of the 20th century, rail grinding is used as a maintenance process and is essential for the increased rail life. In recent years, the surface roughness of railway tracks became increasingly important, especially with respect to the noise emissions. The rail grinding has a positive impact on the quality and life of the railway infrastructure, particularly on the driving comfort and safety. However, for the first weeks after the grinding, residents near railway lines have increased noise emissions from passing trains. This undesirable side-effect is a result of the rough surface left after the grinding process. Only through numerous train crossings are the generated roughness peaks gradually smoothed, whereby the noise emission is reduced. The wheel–rail contact is the dominant noise source at speeds between 50 and 250 km/h. Below those speeds, the propulsion noises outweigh and above 250 km/h the aerodynamic effects outweigh the wheel–rail contact noise emissions. In this paper, a newly developed rail grinding strategy is presented, which improves the roughness of the rail surface and, thus, delivers a reduction of noise emissions immediately after the grinding. The basic development of this new grinding technique was performed as a laboratory test, which will be presented in detail. Furthermore, for a better understanding of the process, the most important technological and kinematic variables are presented. The results of acoustic measurements on a track section, which has been ground with this new technology, will be presented.